2017
DOI: 10.18632/oncotarget.15438
|View full text |Cite
|
Sign up to set email alerts
|

The suppressing effects of BTG3 expression on aggressive behaviors and phenotypes of colorectal cancer: Anin vitroandvivostudy

Abstract: Here, we found that down-regulated expression of BTG3 might be positively correlated with colorectal carcinogenesis and its overexpression suppressed proliferation, glycolysis, mitochondrial respiration, cell cycle progression, migration, and invasion, and induced apoptosis, senescence and differentiation in SW480 and SW620 cells. After treated with cisplatin, MG132, paclitaxel and SAHA, BTG3 transfectants exhibited lower viability and higher apoptosis than the control in both time- and dose-dependent manners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…Our previous study and other reports have demonstrated that BTG3 overexpression suppresses cell proliferation and promotes apoptosis in CRC, epithelial ovarian cancer and esophageal adenocarcinoma [37][38][39][40]. These evidences demonstrate that BTG3 exerts anti-proliferative and pro-apoptotic effects in CRC and other human cancers.…”
Section: Discussionsupporting
confidence: 57%
“…Our previous study and other reports have demonstrated that BTG3 overexpression suppresses cell proliferation and promotes apoptosis in CRC, epithelial ovarian cancer and esophageal adenocarcinoma [37][38][39][40]. These evidences demonstrate that BTG3 exerts anti-proliferative and pro-apoptotic effects in CRC and other human cancers.…”
Section: Discussionsupporting
confidence: 57%
“…Lv et al (2018) found that BTG3 knockdown promoted cell proliferation, migration, invasion, relieved G 2 arrest, and inhibited apoptosis in colorectal cancer cells with PAK2 (p21 activated kinase 2), RPS6KA5 (ribosomal protein S6 kinase A5), YWHAB (tyrosine 3-monooxygenase/ tryptophan 5-monooxygenase activation protein beta), and STAT3 up-regulated and RAP1A (ras-related protein rap-1A), DUSP6 (dual specificity phosphatase 6), and STAT (signal transducer and activator of transcription) 1 down-regulated. Our group demonstrated that BTG3 expression inhibited proliferation, tumor growth, migration and invasion, and induced autophagy, apoptosis, and chemosensitivity to cisplatin, MG132 (proteasome inhibitor), paclitaxel, and SAHA (histone deacetylase inhibitor) in gastric and colorectal cancer cells (Gou et al, 2015;Zheng et al, 2017). In esophageal adenocarcinoma cells, BTG3 upregulation suppressed the proliferation and invasion (Du et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BTG3 mRNA expression was positively linked to the differentiation of gastric cancer, in line with our previous report about gastric cancer tissues (Gou et al, 2015). BTG3 was also reported to induce the differentiation of gastric and colorectal cancer cells, evidenced by a higher level of alkaline phosphatase (Gou et al, 2015;Zheng et al, 2017). These findings suggested that BTG3 mRNA expression might underlie the molecular mechanisms of gastric cancer differentiation.…”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations